2013
DOI: 10.3389/fnsys.2013.00084
|View full text |Cite
|
Sign up to set email alerts
|

Musical expertise and foreign speech perception

Abstract: The aim of this experiment was to investigate the influence of musical expertise on the automatic perception of foreign syllables and harmonic sounds. Participants were Cuban students with high level of expertise in music or in visual arts and with the same level of general education and socio-economic background. We used a multi-feature Mismatch Negativity (MMN) design with sequences of either syllables in Mandarin Chinese or harmonic sounds, both comprising deviants in pitch contour, duration and Voice Onset… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 64 publications
3
19
0
Order By: Relevance
“…This study’s results are consistent with previous investigations on phonetic aptitude and musical expertise (e.g., Schön et al, 2004 ; Thompson et al, 2004 ; Wong and Perrachione, 2007 ; Pastuszek-Lipinska, 2008 ; Milovanov, 2009 ; Nardo and Reiterer, 2009 ; Reiterer et al, 2011 ; Hu et al, 2012 ; Christiner and Reiterer, 2013 ; Martínez-Montes et al, 2013 ). Musicians (instrumentalists and vocalists) were better in imitating unintelligible speech when compared to non-musicians/non-singers.…”
Section: Discussionsupporting
confidence: 92%
“…This study’s results are consistent with previous investigations on phonetic aptitude and musical expertise (e.g., Schön et al, 2004 ; Thompson et al, 2004 ; Wong and Perrachione, 2007 ; Pastuszek-Lipinska, 2008 ; Milovanov, 2009 ; Nardo and Reiterer, 2009 ; Reiterer et al, 2011 ; Hu et al, 2012 ; Christiner and Reiterer, 2013 ; Martínez-Montes et al, 2013 ). Musicians (instrumentalists and vocalists) were better in imitating unintelligible speech when compared to non-musicians/non-singers.…”
Section: Discussionsupporting
confidence: 92%
“…Our finding of a link between rhythm perception and production and second language acquisition is in line with our precursor research which demonstrated that adult second language learners with greater rhythmic sensitivity spoke more fluently (with faster speech rate and fewer pauses and repetitions) (Saito et al, 2018). This relationship between rhythm perception and second language learning may help explain prior findings of links between musical training and second language learning success (Slevc & Miyake, 2006;Martinez-Montes et al, 2013;Swaminathan & Gopinath, 2013;Cooper, Wang, & Ashley, 2017;Dittinger, D'Imperio, & Besson, 2018). Musicians demonstrate enhanced rhythm skills, including more precise synchronization and more accurate rhythm memory (Bailey & Penhune, 2010;Krause, Pollok, & Schnitzler, 2010), which may help them benefit from temporal structure in speech.…”
Section: Discussionsupporting
confidence: 89%
“…Musicians can classify speech sounds (vowels) more easily and quickly than non-musicians (Bidelman et al, 2014), have advantages in relation to the processing of linguistic syntax (Fiveash and Pammer, 2014) and in making judgements about grammar (Patston and Tippett, 2011). They are better able to distinguish rapidly changing sounds (Gaab et al, 2005), harmonic differences (Corrigall and Trainor, 2009;Musacchia et al, 2008;Zendel and Alain, 2009) and tonal variations in non-native speech sounds (Chandrasekaran et al, 2009;Cooper and Wang, 2010;Kühnis et al, 2013;Marie et al, 2011a;Marie et al, 2011b;Marques et al, 2007;Martínez-Montes et al, 2013;Perfors and Ong, 2012;Slevc and Miyake, 2006;Wong and Perrachione, 2007;Yang et al, 2014).…”
Section: Research Comparing Musicians With Non-musiciansmentioning
confidence: 99%